PENGUATAN KARAKTER BERKEBHINEKAAN GLOBAL PADA PEMBELAJARAN PANCASILA MELALUI MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE PESERTA DIDIK KELAS 5 SD NEGERI LIDAH KULON I/464 SURABAYA - Chayul Chusnah, Putri; Sukartiningsih, Wahyu; Asari, Ini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the character of global diversity through the application of the Value Clarification Technique (VCT) Learning Model in Pancasila and Citizenship Education (PPKn) subjects in grade 5 of elementary school. The VCT model is an approach that allows students to clarify their values and attitudes in greater depth. In this research, teachers use the VCT method to help students understand and internalize the values of diversity, tolerance, and cooperation. The research results show that the application of the VCT model significantly increases students' understanding of various aspects of global diversity. Students are better able to recognize cultural differences, appreciate diversity, and interact well in a multicultural environment. Thus, the VCT model can be an effective alternative for developing diverse character in students at the elementary school level.